INTRODUCTION. GONZO SCHOLARSHIP: POLICING ELECTRONIC JOURNALS - Shoaf, R. A. (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
Introductory remarks at the Council of Editors of Learned Journals (CELJ) panel at the MLA in Toronto (1993) whose proceedings are published by Surfaces as Vol. IV 102, 103, 104, etc.. The participants assess the impact of electronic publishing on the scholarly world.